CONCEPTUAL MODEL OF LEARNING MATERIALS ORIENTED TO THE DIMENSIONS OF KNOWLEDGE AND COGNITIVE PROCESSES IN BALANCE AND ROTATIONAL DYNAMICS FOR HIGH SCHOOL PHYSICS LEARNING - Kurnia Andoko; Amali Putra; - Hidayati (PILLAR OF PHYSICS EDUCATION, 2021)
Revolution 4.0 has changed the demands of the world of education a lot. The national education system expects students to develop the potential for thinking in order to keep up with the times. K-13 is used as a solution to answer it so that learning combines the dimensions of knowledge and cognitive processes. Overcome, real conditions found that the learning materials in balance and rotational dynamics used in schools didn’t meet the scope of the dimensions of knowledge and cognitive processes as expected. One solution to this problem is to develop learning materials oriented to the dimensions of knowledge and cognitive processes in balance and rotational dynamics. The purpose of this research is to develop and determine the validity of the dimensions of knowledge and cognitive processes on teaching materials in balance and rotational dynamics for high school physics learning. The type of research is Research and Development by taking the ADDIE model which is reduced to the development stage. The subjects are 3 physics lecturers UNP and 3 physics teachers from SMAN 2, 4, and 12 Kerinci with the object being teaching materials consisting of lesson plans, textbook, and evaluation instruments. The results of data analysis obtained of validity values on lesson plans, textbook, and evaluation instruments according to lecturers and teachers respectively with a score 84,67% and 94,58%. Overall teaching materials get an average score 89,63% in very valid category and can be continued with field tests to determine its practicality and effectiveness in high school physics learning.